Serial turbo decoder for robust communication - Chuah, T.C.; Pu, C.H. (2005)
A new serial turbo decoder for robust communication in the presence of impulsive noise is proposed and examined. The new decoder iteratively performs robust maximum a posteriori (MAP) decoding by cascading a nonlinear MAP inner decoder incorporating a non-quadratic penalty function with an MAP outer decoder. Results show that the proposed serial turbo decoder facilitates considerable performance improvement.